MANAJEMEN HUBUNGAN SEKOLAH DENGAN MASYARAKAT (HUSERMAS) DALAM LEMBAGA PENDIDIKAN - Afiati Fatimah; Rahmat Mulyono (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
Society and schools are an inseparable unit in an effort to educate the nation's children. In fact, both are part of the center of the education tri-center. This study aims to describe the management of public relations (public relations) in developing educational institutions. This study is to analyze and determine the relationship management between schools and the community in educational institutions. This study uses a qualitative descriptive approach with a case study method. The subjects in this study were principals, teachers, the community. Data collection used the methods of observation, interviews, and documentation. The techniques used in conducting data analysis are data reduction, data presentation, and conclusion drawing. The validity of the data is done to explain the data by using source triangulation. Self-evaluation for public relations can be done in various ways, and most importantly can observe and evaluate programs that have been carried out carefully. Such an evaluation is done by focusing on the process and results of a program that has been implemented by public relations. In which the public relations party can evaluate a program after the program has been thoroughly implemented. And at the same time an evaluation is also carried out at the end of the school year by the school management, in order to further strengthen the evaluation of the PR itself